Investigation of an outbreak of Clostridium difficile infection in a general hospital by numerical analysis of protein patterns by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. - Costas, M (1994)
One hundred forty-five cultures of Clostridium difficile, including strains from an apparent nosocomial outbreak of infection, were characterized by one-dimensional sodium dodecyl sulfate-polyacrylamide gel electrophoresis of whole-cell proteins. Each protein pattern was characterized by the presence of one to three dense bands which were highly reproducible. The first 100 strains (in chronological order) were used as the basis for a numerical analysis which divided the strains into 17 phenons (EP types 1 to 17). The protein patterns of the remaining 45 strains were identified to type by comparing their individual patterns against a data base made up of the protein patterns of the first 100 strains. EP type 1 was the most common, with 70 of 139 (50%) patient isolates having this pattern type, and it accounted for 26 of 35 strains (74%) from patients in a medical teaching ward from which the outbreak was believed to have originated. This type was also found as a high proportion of isolations in a number of other medical and oncology wards, but the majority of these isolates occurred subsequent to the isolations on the initial outbreak ward. This technique can therefore provide a method for tracing the possible spread of epidemic strains in hospitals and other institutions and may contribute to a better understanding of the epidemiology of C. difficile.